Passive Protection of Diabetic Rats with Antisera Specific for the Polysaccharide Portion of the Lipopolysaccharide Isolated from Pseudomonas pseudomallei - Larry E Bryan; Sallene Wong; Don E Woods; David AB Dance; W Chaowagul (Canadian Journal of Infectious Diseases)
Polyclonal and monoclonal antisera raised to tetanus toxoid-conjugated polysaccharide of lipopolysaccharide (lps) and purified lps of Pseudomonas pseudomallei that reacted with a collection of 41 strains of this bacterium from 23 patients are described. The common antigen recognized by these sera was within the polysaccharide component of the lps of the cells. The sera were specific for P pseudomallei in that none of 37 strains of other bacteria, including 20 Gram-negative and three Gram-positive species, were recognized, although cross-reaction occurred using the anticonjugate serum with some strains of Pseudomonas cepacia serotype A, a closely related bacterium. Passive protection studies using a diabetic rat model of P pseudomallei infection showed that partially purified rabbit polyclonal and mouse monoclonal antisera were protective when the median lethal dose was raised by four to five orders of magnitude. The wide distribution of the polysaccharide antigen among isolates of P pseudomallei used in this study and the protective role of antibody to the conjugated polysaccharide antigen suggest potential as a vaccine.